Impact Analysis of Ground Traffic and Proposed Jinan Metro Line 6 on Nearby Ancient Brick-wood Structure Vibration - AI Nan; HOU Hetao; WANG Peisen; Chen Juan (Chengshi guidao jiaotong yanjiu)
［Objective］ The vibration impact of ground traffic on nearby ancient buildings is becoming increasingly prominent. It is necessary to analyze the influence of ground traffic and the proposed Jinan Metro Line 6 on the vibration characteristics of the ancient Jiangxi Guild Hall buildings along the line under the typical soil geological conditions of Jinan, so as to evaluate the impact of traffic environmental vibration on ancient buildings of trade guild halls of Ming and Qing dynasties. ［Method］ The ground vibration response under the ground traffic load is measured by the measuring points inside and outside the main hall of Jiangxi Guild Hall, and the influence of the proposed Metro Line 6 on the ancient buildings is calculated by the established tunnel-soil-main hall building model for Jiangxi Guild Hall. The vibration level of the buildings under the separate actions of the above two traffic loads is evaluated according to GB/T 50452—2008 Technical Specification for Protection of Historic Buildings against Man-made Vibration. ［Result & Conclusion］ Under the action of ground traffic load, the vibration of the Jiangxi Guild Hall complex is mainly vertical. The main vibration frequencies along the road direction in different positions inside the building main hall are all greater than those in the direction perpendicular to the road. Under the action of metro loads, the vibration of the Jiangxi Guild Hall building is mainly vertical. The horizontal vibration at the top of the columns decreases compared to that at the bottom of the column, while the vertical vibration increases. The horizontal high-frequency vibration attenuates relatively quickly, while the low-frequency vibration attenuates relatively slowly. Both the vertical high-frequency and low-frequency vibrations attenuate relatively slowly. Under the action of traffic loads and metro loads, the vibration level of the Jiangxi Guild Hall meets the provisions on the vibration limits of ancient wooden structures in the GB/T 50452—2008.